Counseling methodologies for the ethnic minorities in the Philippines. - Rosales, Lily Rosqueta (Education Quarterly, 1984)
The Study concerned itself with the various counselling methodologies (therapeutic approaches) which may used with the following people: the mountain Tinggians of Abra, the Bontoc Igorots of Mountain Province, and the Ibanags of Mongol descent of Cagayan Valley. A Sampling of men, women and youth was made. The men's ages ranges from 35 to 74; the women's ages raged from 25 to 80; the youth based on Dr. Burl Gilliland's classification.